A Case Study: Utilizing My Faith and Racial Minority Status to Deepen Clinical Work. Issue 2 (June 2018) - Huang, Anna
In this article, I briefly describe how my upbringing in the Chinese/Chinese-American church impacted my religious development and my passion for psychology. I discuss a clinical case which highlights the ways I use my own racial minority status and Christian faith to understand transference and counter-transference with another minority, faith-based client. The twinship components between my client and I are explored.